Does Energy Consumption Respond to Price Shocks? Evidence from a Regression-Discontinuity Design - Paulo Bastos; Lucio Castro; Julian Cristia; Carlos Scartascini (Inter-American Development Bank (IDB), 2011)
This paper exploits unique features of a recently introduced tariff schedule for natural gas in Buenos Aires to estimate the short-run impact of price shocks on residential energy utilization. The schedule induces a non-linear and nonmonotonic relationship between households accumulated consumption and unit prices, thus generating an exogenous source of variation in perceived prices, which is exploited in a regression-discontinuity design. The estimates reveal that a price increase in the utility bill received by consumers causes a substantial and prompt decline in gas consumption. Hence they suggest that policy interventions via the price mechanism, such as price caps and subsidies, are powerful instruments to influence residential energy utilization patterns, even within a short time span.
Keywords: L95; D12; L51; Q41; Q48; 330; Energy consumption; Elasticity of demand; Regulation of public utilities; Regression discontinuity design; Public policy